A study of Prevalence and Antimicrobial Susceptibility Pattern of Methicillin Resistant Staphylococcus. - S.SAVITHA; N.YOGANANTH (International Journal of Pharma and Bio Sciences, 2018)
Methicillin-resistant Staphylococcus aureus (MRSA) plays an important role in nosocomial infections including those in communities. It has a remarkable capability of evolving different mechanisms of resistance to most antimicrobial agents .This study reports the prevalence and antibiotic susceptibility pattern of MRSA in tertiary care hospital in Chennai, India. A total of 765 clinical specimens and 113 carrier samples were collected and strains were confirmed by standard bacteriological procedures. Antibiotic sensitivity pattern was carried out by disc diffusion method. Out of 207 strains of S. aureus isolated from clinical and carrier samples, 101(57%) and 19(59%) were found to be MRSA respectively. In clinical MRSA strains, 88% were resistant to penicillin, 71% to ampicillin, 66% towards gentamicin, 63% to co-trimoxazole, and Erythromycin. Most of the MRSA strains (84.2%) of carrier screening samples had resistance to penicillin and about 73.6% were resistant to ampicillin and Ofloxacin, 66% resistant towards co-trimoxazole respectively. Multidrug resistance was observed among 63.6% of clinical and 23% of carrier MRSA isolation. No isolates was found resistant to vancomycin. The determination of prevalence and antibiotic sensitivity pattern of MRSA will help the treating clinicians effectively and preventing irrational use of antibiotics.